131k views
1 vote
1/2x - 5/4 + 2x = 5/6 + x

1/2x - 5/4 + 2x = 5/6 + x-example-1
User Fenil
by
6.0k points

2 Answers

2 votes

Answer:

12

Explanation:

edge

User Jared Reeves
by
4.8k points
0 votes

25/18

Explanation:

The given equation is a simple algebraic equation with only one unknown variable
x.


(1)/(2)x-(5)/(4)+2x=(5)/(6)+x

Let us take all the
x containing terms to left hand side and remaining terms to right hand side.


(1)/(2)x+2x-x=(5)/(4)+(5)/(6)


((1)/(2)+1)x=(5* 6+5* 4)/(6* 4)


(3)/(2)x=(50)/(24)


x=(50)/(36)=(25)/(18)


x=(25)/(18)=1.39

The given options must be wrong.

User Guile
by
5.9k points